2012
DOI: 10.1111/jsr.12006
|View full text |Cite
|
Sign up to set email alerts
|

Altered cortical and subcortical local coherence in obstructive sleep apnea: a functional magnetic resonance imaging study

Abstract: SUMMARYObstructive sleep apnea (OSA) syndrome is the most common sleeprelated breathing disorder, characterized by excessive snoring and repetitive apneas and arousals, which leads to fragmented sleep and, most importantly, to intermittent nocturnal hypoxaemia during apneas. Considering previous studies about morphovolumetric alterations in sleep apnea, in this study we aimed to investigate for the first time the functional connectivity profile of OSA patients and age-gender-matched healthy controls, using res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 30 publications
5
48
0
Order By: Relevance
“…Previous studies on brain resting‐state FC in OSA subjects found local FC alterations in the middle and dorsal prefrontal cortex, left precentral gyrus, and PCC, decreased local FC in the frontal, temporal, and parietal, and increased FC in the sensorimotor, thalamic, and cerebellum regions (Santarnecchi et al. ; Zhang et al. ; Peng et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies on brain resting‐state FC in OSA subjects found local FC alterations in the middle and dorsal prefrontal cortex, left precentral gyrus, and PCC, decreased local FC in the frontal, temporal, and parietal, and increased FC in the sensorimotor, thalamic, and cerebellum regions (Santarnecchi et al. ; Zhang et al. ; Peng et al.…”
Section: Discussionmentioning
confidence: 94%
“…), and compromised resting‐state regional activity using regional homogeneity (Santarnecchi et al. ; Peng et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen publications that recruited 290 OSA patients and 290 healthy controls were included (Ayalon et al, 2009a, Ayalon et al, 2006, Fatouleh et al, 2014, Harper et al, 2003, Henderson et al, 2003, Joo et al, 2010, Li et al, 2015, Macey et al, 2006, Macey et al, 2003, Morrell et al, 2010, Prilipko et al, 2011, Santarnecchi et al, 2013, Torelli et al, 2011, Yaouhi et al, 2009, Zhang et al, 2013) (Table 1, Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recent rs-fMRI studies also demonstrate functional disconnection in brain areas of the CEN and DMN in OSA patients [6,51]. These findings suggest that the functional impairment of the CEN and DMN may contribute to cognitive deficits in these patients.…”
Section: Page 14 Of 29mentioning
confidence: 91%